Issues and Best Practices in Content Analysis. - Lacy, Stephen; Watson, Brendan R.; Riffe, Daniel; Lovejoy, Jennette (Journalism & Mass Communication Quarterly)
This article discusses three issues concerning content analysis method and ends with a list of best practices in conducting and reporting content analysis projects. Issues addressed include the use of search and databases for sampling, the differences between content analysis and algorithmic text analysis, and which reliability coefficients should be calculated and reported. The “Best Practices” section provides steps to produce reliable and valid content analysis data and the appropriate reporting of those steps so the project can be properly evaluated and replicated.